Launching protostellar jets from finite-radius accretion disks - Stute, Matthias; Gracia, Jose; Vlahakis, Nektarios; Tsinganos, Kanaris (Protostars and Planets VI Posters, 2013)
Analytical radially self-similar models are the best available solutions describing disk-winds, but they need several improvements. We introduce models of jets from truncated disks, i.e. numerical simulations based on a radially self-similar MHD solution but including the effects of a finite radius of the jet-emitting disk, hence the outflow. We compare these models with available observational data, by varying the jet density and velocity, the mass of the protostar, the radius of this truncation and the inclination. In order to our models with observed jet widths inferred from recent optical images taken with HST and ground-based AO observations, we create emission maps in different forbidden lines, and from such emission maps, determine the jet width as the full-width half-maximum of the emission. We can reproduce the jet widths of several examples and its variations very well. We conclude that truncation - i.e. taking the finite radius of the jet launching region into account - is needed to reproduce the observed jet widths, and our simulations limit the possible range of truncation radii. The effects of inclination are important for modeling the intrinsic variations seen in observed jet widths. Our models can be used to infer the inclinations in the observed sample independently.